EFEKTIVITAS SPIRITUAL HEALING TERHADAP PENURUNAN TINGKAT KECEMASAN PADA WANITA MENOPAUSE - Yuliani, Ulfah Dwi; Akbid YLPP Purwokerto, Sugi Purwanti (Jurnal Kebidanan)
<!–[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> ABSTRACT Spiritual healing is a healing process through improvement of the body’s energy system and rokhani with method of tapping in some specific points on the body. In addition to the energy system of the body there is also a method of relaxation with a confidence factor involved can reduce anxiety. This research aims to knowing the effectiveness of spiritual healing in lowering the level of anxiety to menopausal women kelompok pengajian Majelis Taklim Nurul Hikmah Purbadana village Kembaran sub-district Banyumas district 2013. The kind of this research is by using quasi-experiment with Time series design sampling techniques using the quota sampling, the sample number of 32 people. Therapi spiritual healing is given once every 1 weeks for 3 consecutive weeks, before and after the intervention be a assessment of the level of anxiety using a questionnaire HARS (Hamilton Anxiety Rating Scale), all data collected is analyzed with a Wilcoxon test with significant level (Î± = 0.05 level). The known research results : Indicates that the value of p = 0.000 < 0.05 it means that the value of asymp sig < value of Î± , it means H0 is rejected indicates that Spiritual healing provide a positive influence on the decrease in the level of anxiety to menopausal women. The conclusion of this research Spiritual healing is effective to decrease the level of anxiety to menopausal women kelompok pengajian Taklim Nurul Hikmah in Purbadana Village which belongs to Kembaran Sub-district in Banyumas district Keywords : Anxiety, Menopause, spiritual healing <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–>